2022
DOI: 10.1039/d2py00290f
|View full text |Cite
|
Sign up to set email alerts
|

Scandium-catalyzed stereoselective block and alternating copolymerization of diphenylphosphinostyrenes and isoprene

Abstract: The coordination copolymerization of polar diphenylphosphinostyrenes (StPPh2) and isoprene (IP) by a half-sandwich scandium catalyst (C5Me4SiMe3)Sc(CH2C6H4NMe2-o)2 afforded a new series of phosphine-functionalized alternating and block isoprene-styrene copolymers. In the copolymerization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These properties lead to exclusive formation of the alternating o ‐StPPh 2 ‐St copolymer (poly( o ‐StPPh 2 ‐ alt ‐St)) before all the o ‐StPPh 2 was consume and also leads to formation of alternating and block copolymers poly( o ‐StPPh 2 ‐ alt ‐St)‐ b ‐ s PS after all the o ‐StPPh 2 was consume (Scheme 1). [14–16,22,24,26] …”
Section: Resultsmentioning
confidence: 99%
“…These properties lead to exclusive formation of the alternating o ‐StPPh 2 ‐St copolymer (poly( o ‐StPPh 2 ‐ alt ‐St)) before all the o ‐StPPh 2 was consume and also leads to formation of alternating and block copolymers poly( o ‐StPPh 2 ‐ alt ‐St)‐ b ‐ s PS after all the o ‐StPPh 2 was consume (Scheme 1). [14–16,22,24,26] …”
Section: Resultsmentioning
confidence: 99%
“…For example, the co-ordination copolymerization of polar diphenylphosphine styrene ( p -StPPh 2 ) and IP was conducted using a half-sandwich scandium (C 5 Me 4 SiMe 3 ) Sc (CH 2 C 6 H 4 NMe 2 - o ) 2 catalyst. Notably, p-StPPh 2 was incorporated into the polymer chains after the almost complete depletion of IP, resulting in the synthesis of phosphine-functionalized 1,4/3,4-isoprene-styrene block copolymers [ 21 ]. The recent study also presents examples of 3,4-PI- b -polycaprolactone block copolymers prepared through the sequential addition of hard ε -caprolactone to the living lutetium (Lu)−PI active species, followed by ring-opening polymerization [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in the research on polar monomer insertion reaction, a significant amount of successful experimental work has been carried out. Hou et al [22][23][24][25][26] demonstrated that cationic half-sandwich rare earth metal aminobenzyl complexes are highly effective in catalyzing the insertion reactions of halogenated or amino-containing styrene monomers. Cui et al [27][28][29][30][31] developed constrained-geometry-configuration rare-earth metal complexes that effectively catalyze the insertion reactions of methoxystyrene monomers, ethyl vinyl ether, and other polar monomers, showing high catalytic activity and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%